A review of composite bipolar plates in proton exchange membrane fuel cells: Electrical properties and gas permeability. (15th April 2021) - Jeong, Kwang Il; Oh, Jaehyung; Song, Seung A; Lee, Dongyoung; Lee, Dai Gil; Kim, Seong Su
Abstract: Proton exchange membrane fuel cells (PEMFCs) consist of bipolar plates, end plates, membrane electrode assemblies, and gas diffusion layers. Among these components, the bipolar plates (BPs) are the main components because they contribute significantly to the volume, cost, and weight of the PEMFC. Owing to their good electrical and thermal conductivities, graphite and metallic materials are conventional materials for BPs. However, graphite BPs lack mechanical strength, and it is difficult to machine channels on these BPs due to the intrinsic brittleness of the material. Metallic BPs have relatively high density and require surface modification and coating to suppress surface corrosion. Recently, thermoplastic or thermosetting composites reinforced with carbon-based conductive fillers have attracted significant attention because of their superior corrosion resistance and low density. In this paper, we comprehensively review the electrical conductivities of composite BPs in terms of their carbon-based fillers, matrix materials, and the manufacturing process. Next, various surface treatments aimed at improving the interfacial contact resistance of composites are discussed. Finally, methods used for reducing gas permeabilities of composite BPs are summarized.